2001
DOI: 10.1111/j.1744-7429.2001.tb00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Patterns of Migrant and Resident Birds in Successional Forests of the Yucatan Peninsula, Mexico1

Abstract: Increasing human activity in the Yucatan peninsula has led to declines in older stages of successional forest, threatening regional habitat diversity. To determine potential effects of this habitat loss on the region's avifauna, we examined the relative use of different forest stages by resident and migrant birds during the nonbreeding season. We used the fixed‐width transect method to compare the distribution, abundance, and diversity of forest birds in early (five to ten years old), mid (15–25 years), and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 47 publications
4
28
1
6
Order By: Relevance
“…Por otra parte, aunque se ha considerado que ambientes maduros (e.g., selvas) son muy diversos (Blake & Loiselle 2001), varios investigadores han señalado que tanto la riqueza como la abundancia y diversidad de especies es similar en etapas de sucesión tempranas y maduras (Andrade & Rubio 1994, Petit et al 1995, Smith et al 2001. Por ejemplo, los resultados aquí presentados varían de acuerdo a lo reportado por Robinson & Terborgh (1997) y Blake & Loiselle (2001) en selvas altas de Costa Rica, en donde selvas en regeneración presentaron mayor riqueza y abundancia de especies de aves que la selva madura.…”
Section: Discussionunclassified
“…Por otra parte, aunque se ha considerado que ambientes maduros (e.g., selvas) son muy diversos (Blake & Loiselle 2001), varios investigadores han señalado que tanto la riqueza como la abundancia y diversidad de especies es similar en etapas de sucesión tempranas y maduras (Andrade & Rubio 1994, Petit et al 1995, Smith et al 2001. Por ejemplo, los resultados aquí presentados varían de acuerdo a lo reportado por Robinson & Terborgh (1997) y Blake & Loiselle (2001) en selvas altas de Costa Rica, en donde selvas en regeneración presentaron mayor riqueza y abundancia de especies de aves que la selva madura.…”
Section: Discussionunclassified
“…This assumption is based on previous large-scale secondary studies indicating a negligible effect on bird diversity [e.g., [39][40][41][42], whereas other studies [19,43] have shown that diversity is affected in small-scale studies that do not make up a matrix of surrounding primary (or close to primary) habitats and edge habitats. While the short duration of our survey and the sampling limitations intrinsic to the sampling design used recommend caution with the interpretation of the data presented, the results suggest that shifting cultivation fallows seem to have similar abundances but different richness of bird species compared to primary forest.…”
Section: Discussionmentioning
confidence: 99%
“…We also hypothesized that the responses of resident and migratory bird species should differ in each of the management units. Resident bird species should present larger differences in their communities among management units than Neotropical migrants because they have to confront the existing habitat conditions throughout the year, while migrants can act as habitat generalists because they use different environments in different seasons (Hutto, 1989;Lynch, 1989;Levey, 1994;Smith et al, 2001).…”
Section: Introductionmentioning
confidence: 99%